Program Dakwah ‘Serambi Islami’ di TVRI Perspektif Audience And Users - Abdul Jalil (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2021)
The purpose of this study is to find out how the "Serambi Islami" da'wah program on TVRI is from the perspective of the audience and users? The author chose TVRI, because of its existence as the oldest state-owned television with a mission to provide information, provide entertainment, and facilitate education for the community. The theory used in this study is from audience to users proposed by Gill Branston and Roy Stafford. This research is a field study using a descriptive method and a qualitative approach. Serambi Islami is a religious program on TVRI that airs from 04.30 to 06.00, every day from Monday to Sunday. This program is intended for all people who want to watch propaganda shows. To convey the messages of da'wah, an effective media is needed. Television is a strategic mass media as a means of da'wah. This media is very popular in the community that can reach audiences and users to remote areas. Presentation of da'wah materials on television that are weighty and attractive is an important part, so that viewers are interested in as objects of da'wah (mad'u).